2018
DOI: 10.1007/s11255-018-1857-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of hypertension and diabetes after exposure to extracorporeal shock-wave lithotripsy in patients with renal calculi: a retrospective non-randomized data analysis

Abstract: PurposeTo evaluate the association of shock-wave lithotripsy (SWL) for kidney stones and hypertension or diabetes.MethodsPatients with urolithiasis treated by SWL were retrospectively identified. To assess whether shock-wave application to the kidney is associated with long-term adverse effects, patients after SWL for kidney stones were selected as the main group of interest. Patients treated with shock waves for distal ureter stones only were chosen as a comparison group. A questionnaire was sent to all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…After ESWL, several complications, such as hematuria, renal hematoma, renal ureteral injury, renal colic, stone street formation, and urinary tract infection, may occur ( 27 ). The most frequent complication after ESWL treatment is ureteric obstruction induced by the stone fragments.…”
Section: Literature Searchmentioning
confidence: 99%
“…After ESWL, several complications, such as hematuria, renal hematoma, renal ureteral injury, renal colic, stone street formation, and urinary tract infection, may occur ( 27 ). The most frequent complication after ESWL treatment is ureteric obstruction induced by the stone fragments.…”
Section: Literature Searchmentioning
confidence: 99%
“…Дистанционная ударно-волновая литотрипсия (ДЛТ) в настоящее время применяется ограниченно, в связи с высоким уровнем осложнений. Особенно при наличии у пациента гипертонии и сахарного диабета [3]. Чрескожные пункционные доступы (ПНЛ) сопровождаются высоким риском значимой кровопотери и более длительным периодом реабилитации, в сравнении с уретероскопией [4].…”
Section: ключевые слова: мочекаменная болезнь уролитиаз литотрипсия л...unclassified
“…However, in more recent years, SWL renown has been challenged by the widespread diffusion of endourology; together, as time goes by, some concerns on long-term safety of SWL have been raised as well. Hypertension and diabetes are regarded as possible long-term drawbacks, and their risk after SWL has been addressed by a recent manuscript from Fankauser et al [2]. Authors reported in 2018 on the prevalence of hypertension and diabetes-assessed with a questionnaire mailed in 2015-in a series of 764 patients treated with SWL between 1993 and 2013.…”
mentioning
confidence: 99%